Developmental disabilities related education, technical assistance and research activities in developing nations - Davidson, Philip W., and others
Different models for international activities in mental retardation and developmental disabilities are described, as well as principles that characterize successful international programmes. A case study of an international exchange and technical assistance project conducted between a University Affiliated Programme and Antigua and Barbuda, is offered
Keywords: Developmental disabilities